Reconfigurable Surfaces Based on Photocontrolled Dynamic Bonds. (29th December 2019) - Liu, Jiahui; Butt, Hans‐Jürgen; Wu, Si
Abstract: Photocontrolled surfaces have attracted increasing interest because of their potential applications in lithography, photopatterning, biointerfaces, and microfluidics. Light provides high spatiotemporal resolution to control functions of such surfaces without getting into direct contact. However, conventional photocontrolled surfaces can only be switched between two states (on and off). The development of photocontrolled reconfigurable surfaces that can be switched among multiple states is highly desirable because these surfaces can adapt to rapid environmental changes or different applications. Herein, recent developments of photocontrolled reconfigurable surfaces are reviewed. Specially, reconfigurable surfaces based on photocontrolled reversible reactions including thiol‐quinone methide, disulfide exchange, thiol‐disulfide interconversion, diselenide exchange, and photosubstitution of Ru complexes are highlighted. As a perspective, other photocontrolled dynamic bonds that can be used to construct reconfigurable surfaces are summarized. Remaining challenges in this field are discussed. Abstract : Photocontrolled reconfigurable surfaces that can be switched among multiple states are reviewed. Dynamic bonds that are suited to construct such surfaces are summarized. The principles for the design of photocontrolled reconfigurable surfaces are discussed. Their potential applications including controlling adsorption of biomaterials, switching wettability, rewriting patterns, and guiding liquid motions are highlighted.